REALISTIC MATHEMATIC EDUCATION ON HIGHER-ORDER THINKING SKILL MATHEMATICS OF STUDENTS - Chelsi Ariati; Dadang Juandi (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
The literature on the effect of the Realistic Mathematics Education (RME) approach on high-order thinking skills (HOTS) students is massive. There is a diversity of research results. So a systematic and comprehensive review is needed to justify and describe its effect, which includes problem-solving, critical, creative, and reasoning abilities. This research used a systematic literature review (SLR) technique to search the Semantic Scholar, ERIC, Google Scholar database, and direct URLs from 2013 to 2022, yielding 49 studies that matched the inclusion criteria. Every paper was recorded and then categorized for analysis based on the title, education level, year of publication, sample size, and kind of HOTS. The findings indicated that RME positively impacted students' HOTS when learning activities were applied with student-centered, contextual problems, and the teacher was the facilitator. Working together in small groups allowed students to carry out individual exploration activities, reconstruct concepts from their own experiences, and connect these concepts to the mathematical ideas studied. RME thus becomes appropriate for use in achieving learning's aims and urgency, particularly in raising students' mathematical HOTS. The study's findings also offer information on the trends and heterogeneity of research into applying RME on mathematical HOTS in Indonesia. It is thus anticipated that it will serve as a recommendation and a focus for further study.